Uma Proposta de Ferramenta de Apoio ao Ensino Prático de Computação Ubíqua - Peixoto, Maria Joelma Pereira; Carvalho, Windson Viana de; Sarmento, Wellington Wagner Ferreira (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
Study of Ubiquitous Computing concepts began in various universities, in courses related to Computer Science, which sought to develop the study of ubiquitous systems and technologies. In general, these courses have practical classes or even small ubiquitous application development projects. However, one of the greatest difficulties in teaching Ubiquitous computing is putting into practice the theoretical knowledge acquired since the existing tools already require high-level programming skills or are not designed for educational purposes. As a result, this proposal for master’s thesis aims to design, develop and evaluate a tool that helps to teach practical classes involving concepts of Ubiquitous Computing.